Toeplitz Operators with IMOs Symbols between Generalized Fock Spaces - Yiyuan Zhang; Guangfu Cao; Li He (Journal of Function Spaces)
In this paper, we study the mapping properties of Toeplitz operators Tf associated with IMOs  symbols f acting between two generalized Fock spaces Fφp, where 1<s≤∞. We characterize bounded or compact Toeplitz operators Tf from one generalized Fock space Fφp to another Fφq, respectively, in four cases.